State of Mind in Civil Cases - Charles Claflin Allen (Washington University Law Quarterly, 1957)
This Article will attempt to discuss the main principles concerning the legal effect of different states of mind and will include a brief study of specific applications of these principles to a fev fields of the law of torts, including slander and libel, malicious prosecution, fraud and deceit and the question of liability for punitive damages, and will also consider state of mind as an element in fraudulent conveyances. This discussion will be confined, however, to normal states of mind and will not include states of mind created by insanity or other mental incapacity, or the effect of duress upon an otherwise normal mind.
Keywords: Torts